PLOT SIZE AND SHAPE FOR FIELD TRIALS WITH FORAGE CACTUS PEAR - GUIMARÃES, Bruno Vinícius Castro; DONATO, Sérgio Luiz Rodrigues; ASPIAZÚ, Ignacio; AZEVEDO, Alcinei Místico; CARVALHO, Abner José de (Brazilian Journal of Biometrics, 2021)
This study aimed to determine the size and shape of experimental plots that provide maximum precision using relative information method. This trial was conducted at the Federal Institute of Bahia. Plant height, cladode length, cladode width, cladode thickness, cladode area, cladode area index, number of cladodes, cladode total area and yield were measured in the third production cycle, 930 days after planting. The plants, defined as basic units, were arranged in 39 plot sizes so that the crop would fill the whole experimental area. Then, plot shapes with higher relative information and equal plot size in basic units were selected. The experimental plot with eight basic units in size ensures higher efficiency in the experimental evaluation. This combination between size and shape, besides meeting all evaluation requirements of the characteristics normally assessed in studies with forage cactus pear, has the maximum control of soil heterogeneity, thereby decreasing experimental error and significantly increasing precision.